BIOCLIMATIC ARCHITECTURE AS A DESIGN APPROACH WITH A MIDDLE APARTMENT IN SURABAYA AS A CASE STUDY - Johanes Krisdianto; Agustinus Adib Abadi; Agus Suharjono Ekomadyo (Journal of Architecture&ENVIRONMENT, 2011)
Bioclimatic architecture as a design approach takes an advantage climate parameters to answer the problems of environment and energy. This approach is applied to optimize the quality of architectural design through the comfort and health of their environment. It was developed by simulating the design in the case of a middle apartment in Surabaya. To achieve its design goals is simulated: 1) transforming mass-form, 2) setting housing-unit plan, 3) making housing-unit facade, and 4) organizing overall lay-out. Simulation of this design is using several alternative designs to obtain an optimal design. Bioclimatic architecture is successfully implemented if it can optimize the potential of the existing climate. Bioclimatic quality is achieved when a middle apartment is designed to optimize penetration of natural light, cooling and air exchange building mass as well as minimize the acquisition of direct solar radiation. Bioclimatic architecture approach requires consideration of such architectural contexts: urban, economic and social aspects, because the technical nature.